Partisipasi Perempuan Dalam Proses Pengambilan Keputusan Di Dewan Adat Terkait Dengan Penyelesaian Kasus-Kasus Kekerasan Terhadap Perempuan: Kisah Dari Atambua, Sumba Timur, Rote Dan Labuan Bajo - Nurtjahyo, Lidwina Inge (Jurnal Hukum & Pembangunan, 2020)
Based on Convention on Elimination of Discrimination Against Women, especially in Articles 2c, 5a, 7b and c, 15 (1) and (2) women and men are equal. If there are any discriminations, the states which have ratified the Convention shall eliminate the discriminations from rules or tradition or practices. Women in some indigenous communities have some limitation in decision making process, even in the process to get solution in violence aghaainst women cases. For examples in Rote, Labuan Bajo, East Sumba and Atambua (East Nusa Tenggara) women have limited access to the decision-making process in indigenous forums even in cases of violence against women. This paper will focus on some issues: the limitation itself and the strategies of the women in confronting those restrictions. Data in this paper are collected from literature research, participatory observation, interview with customary councils, interview with some women survivors, interview with government officers and police, from 2015-2018.